Deposit in Caseros - moarqs (ARQ)
American territories are shaped not only by geography but by the ways they are inhabited, which, over time, form a material identity in which we are submerged. Located in Buenos Aires' metropolitan area, Deposit in Caseros exemplifies this principle through the revitalization of the urban fabric with simple, ubiquitous materials rooted in the city’s history. Ultimately, while addressing programmatic challenges, the project contributes to resisting the decline of the city’s industrial identity.